(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The therapeutic potential of Boerhavia diffusa (Punarnava) root extract in managing eye diseases is explored in this study. Recognized for its antioxidant, anti-inflammatory, and immunomodulatory properties, Boerhavia diffusa holds promise as a treatment for ocular conditions such as cataracts, diabetic retinopathy, and age-related macular degeneration. The research focuses on the development of a novel Ayurvedic eye drop formulation using aqueous distillate from Boerhavia diffusa roots, complying with Indian Pharmacopoeia standards. Phytochemical analyses, including HPTLC, GC-MS, and HPLC, confirmed the presence of bioactive compounds like beta-sitosterol. The formulation was evaluated for sterility, stability, and efficacy in delaying cataract formation using in vivo models. Results indicated that the eye drop significantly postponed cataract progression, with no observed ocular irritation or adverse effects. This study highlights the potential of integrating traditional Ayurvedic knowledge with modern pharmaceutical approaches for effective ocular therapies.